The Impact of Covid-19 on Organizational Culture: Sultan Qaboos University Case Study - Aieman Ahmad AL-Omari; Khalaf Marhoun Al'Abri (Ali Khorsandi Taskoh, 2021)
The present study aimed to explore the impact on working culture due to pandemic caused by Covid-19, and whether there were statistically significant sex and experience differences in Sultan Qaboos University staff perceptions. The current study used a questionnaire that applied to a sample consist of 156 staff, of whom 100 were males, and 56 were females. The results of the questionnaire indicated that staff perception the organizational culture during covid-19 pandemic with moderate level. According to sex variable, (13) items of organizational culture during covid-19 pandemic had significant differences from staff perceptions on organizational culture during covid-19 pandemic referred to male, while (3) items had no significant differences. Regarding to staff experience, five of 16 items were significantly differences according to staff experience.